2020
DOI: 10.3389/fphys.2020.606811
|View full text |Cite
|
Sign up to set email alerts
|

Increased (Pro)renin Receptor Expression in the Hypertensive Human Brain

Abstract: Overactivation of the renin-angiotensin system (RAS)-a central physiological pathway involved in controlling blood pressure (BP)-leads to hypertension. It is now well-recognized that the central nervous system (CNS) has its own local RAS, and the majority of its components are known to be expressed in the brain. In physiological and pathological states, the (pro)renin receptor (PRR), a novel component of the brain RAS, plays a key role in the formation of angiotensin II (Ang II) and also mediates Ang II-indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The results were consistent with previous studies in several peripheral tissues showing pro-oxidative and pro-inflammatory effects after PRR activation [ 45 , 46 , 47 ]. In the brain, PRR was observed in neurons and microglial cells [ 17 , 18 , 19 ], and at low levels [ 18 , 19 ] or undetectable [ 17 , 48 , 49 ] in astrocytes. To investigate if the increase in PRR expression in the pro-inflammatory state was related to neurons or microglial cells, we isolated microglial cells, using anti-CD11 microbeads and neurons, using laser microdissection, from brains of adult AT2 KO mice, and we detected a significant increase in PRR expression in microglial cells but not in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The results were consistent with previous studies in several peripheral tissues showing pro-oxidative and pro-inflammatory effects after PRR activation [ 45 , 46 , 47 ]. In the brain, PRR was observed in neurons and microglial cells [ 17 , 18 , 19 ], and at low levels [ 18 , 19 ] or undetectable [ 17 , 48 , 49 ] in astrocytes. To investigate if the increase in PRR expression in the pro-inflammatory state was related to neurons or microglial cells, we isolated microglial cells, using anti-CD11 microbeads and neurons, using laser microdissection, from brains of adult AT2 KO mice, and we detected a significant increase in PRR expression in microglial cells but not in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Overactive brain local renin-angiotensin system (RAS), oxidative/nitrosative stress, and neuroinflammation in concert play a pivotal role in triggering augmenting sympathetic activity in the centers. [8][9][10][11][12] We previously reported that stress induced mitochondrial damage in the microglia of RVLM. 13,14 Microglial mitophagy-lysosome dysfunction mediates the activation of intracellular NLRP3 inflammasome in stress hypertension mice, thus promoting the release of proinflammatory factors.…”
Section: Introductionmentioning
confidence: 95%
“…The expression of PRR in neurons of the paraventricular nucleus (PVN) and rostral ventrolateral medulla (RVLM) was significantly increased in hypertensive humans and positively correlated with systolic BP, 146 implying a key role of the PRR in the PVN and RVLM in the neural regulation of BP in humans. Along with this line, increasing evidence from animal models has shown that PRR plays an essential role in brain AngII formation independently of circulating signals that control BP.…”
Section: Prr Exhibits Hypertensiveaction Via Sprr Generation?mentioning
confidence: 99%